2004
DOI: 10.1088/0022-3727/37/14/006
|View full text |Cite
|
Sign up to set email alerts
|

Axial mercury segregation in direct current operated low-pressure argon–mercury gas discharges: Part I. Experimental

Abstract: Due to cataphoresis, axial segregation of mercury will occur when the gas discharge of a fluorescent lamp is operated by means of a direct current. A consequence of this is a non-uniform axial luminance distribution along the lamp. To determine the degree of axial mercury segregation experimentally, axial luminance distributions have been measured which are converted into axial mercury vapour pressure distributions by an appropriate calibration method. The mercury segregation has been investigated for variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…To describe our experimental results [1], none of the models mentioned earlier proved to be applicable. From our experiment it has been concluded that the mercury vapour pressure gradient is a function of the local mercury vapour pressure.…”
Section: Existing Models and Their Applicabilitymentioning
confidence: 96%
See 4 more Smart Citations
“…To describe our experimental results [1], none of the models mentioned earlier proved to be applicable. From our experiment it has been concluded that the mercury vapour pressure gradient is a function of the local mercury vapour pressure.…”
Section: Existing Models and Their Applicabilitymentioning
confidence: 96%
“…The existing (theoretical and experimental) literature on cataphoresis in low-pressure gas discharges will be reviewed according to the following subdivision: (1) experiments in gas discharges without mercury, (2) experiments in mercury-noble gas discharges, (3) existing models and their applicability.…”
Section: Literature Overviewmentioning
confidence: 99%
See 3 more Smart Citations